Sedimentary characteristics of tidal flats and coastline changes in Ca Mau coastal area, Mekong River Delta - Lap, Nguyen Van; Oanh, Ta Thi Kim (Vietnam Journal of Earth Sciences, 2012)
Sedimentary characteristics, formation and development of tidal flats in relation to Holocene evolution of Mekong river delta are clarified. Morphologically, eastern tidal flats are uneven with the high slope, small area which characterize for erosive coast; western tidal flats in Camau Cape area are even with large width and area which characterize for depositional coast. Camau Cape tidal flats are the largest tidal flat in the Mekong river delta mainly consisted of soft silty clay and have a tendency to expand southwestward.Coastline change of Ca Mau province is identified from 1904 to 2002 on the bases of maps and satellite image interpretations. Erosion occurred strongly in the east coast from Ganh Hao to Khai Long. Total eroded area is 280km2 with average rate of 26-30m/yr, particularly 50-67m/yr at Bo De river mouth. Deposition occurred in the west coast, total deposited area from Xom Mui to Hon Da Bac is 248km2 in which the section from Xom Mui to the south of Bay Hap river mouth has the largest area around 168km2 with average depositional rate of 52-96m/yr.